Hubungan Riwayat Pola Menyusui, Usia Penyapihan dan Emotional Bonding terhadap Status Gizi pada Balita - Habo Abbas, Hasriwiani; Wulandari, Nur Alifah; Lestari, Ayu; Burhanuddin, Nurfardiansyah (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Human quality is a harmonious and balanced blend between physical, mental (spiritual) and social. One of the determinants of human quality is the fulfillment of nutritional needed through foods that contain nutrients needed by humans. Nutrition has an important dimension in improving the quality of human resources. Related research analyzes the factors associated with emotional bonding to nutritional status in children under five in. This type of research is an observational analytic using cross-sectional studies, in the Bontorannu Kelurahan, Mariso District, Makassar City. The sample is non-random sampling: purposive sampling. The results showed the nutritional status of under-fives as many as 90 toddlers (60%), while the nutritional status of under-fives which were 60 toddlers (40%), there was a relationship of research on nutritional patterns to nutritional status where p = 0,000 <Î± = 0.05 with the number toddlers by estimating eating patterns lacking 66.7% and sufficient 33.3%. The age of weaning under five with less than 75 (83.3%), while 15 (16.7%) were sufficient. From the results of statistical tests there is a relationship between age and nutritional status of children. For unsafe emotional ties as many as 36 children under five (17.3%) and safe as many as 114 children under five (82.7%). From the statistical test results obtained there is a relationship of emotional ties to the nutritional status of children under five where p = 0,000 <Î± = 0.05. The warmth that arises from breastfeeding assistance in a pattern of help that supports and supports the bond between mother and baby. This is a natural way to feed baby so it improves the nutritional status of children and provides a very strong emotional closeness.